PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS XII IPA 2 SMA NEGERI 8 PEKANBARU TP. 2016 / 2017: Application of Discovery Learning Learning Model in Improving Economic Learning Results Class XII IPA Student 2 SMA N 8 Pekanbaru Academc Year 2016/2017 - Darmina Darmina (UIR Press, 2019)
This research is motivated by a lack of students 'ability to master the concepts in Economics subjects, this is indicated by many students who score below the determined KKM, namely 76. The students' ability to master the concept is low because the ongoing learning process is teacher-centered where learning is only emphasize students to memorize material only, so as not to provide opportunities for students to construct their own knowledge through their learning experiences. This study tries to apply the discovery learning model. The purpose of this study is to improve student learning outcomes through the application of Discovery Learning Learning models in Economic subjects in class XII IPA-2 Pekanbaru 8 High School. The method used in this study is the class action research method (CAR). Where in this study there are three variables, namely input variables, process variables, and output variables. The research procedure consists of the planning stage, the implementation phase of the action, the observation and evaluation stage, and the analysis and reflection stages. Data collection techniques in this study were taken by using student activity observation sheets and teacher activity observation sheets, as well as evaluating the material taught in each cycle. The subjects in this study were students of class XII IPA-2 Pekanbaru 8 High School, amounting to 35 people and this study was devoted to Economics subjects. Based on the results of this study indicate that the improvement of the learning process and student learning activities that have an impact on student learning outcomes can be shown in the first cycle of student learning outcomes, from the results of analysis used, students who complete the economic learning process in Kejra Paper and Adjustment Journal material, from 35 students were subjected to action, 26 students completed learning with a percentage of 74.28% and students who received an unfavorable category were 9 students with a percentage of 25.71%, of the 9 students 6 students who were in the very good category 17,14 %, whereas in cycle II where 35 students were subjected to action, 34 of them were in very good category, had reached completeness namely 97.14% while those that were still not completed were only 1 student, which was 2.86%. Thus the hypothesis that reads If applied to the Learning Learning Model Learning in Economic subjects in class XII IPA-2 Pekanbaru 8 High School, will increase and be accepted.Keywords: Learning Outcomes, Discovery Learning Learning Models in Economics subjects